Features of the Implementation of the Principle of Proportionality in the Use of Force - Aleksanyan, Kristine (Bulletin of Yerevan University C: Jurisprudence, 2024)
The article is devoted to the development of the features of the application of the principle of proportionality in the case of the "use of force". The article touched upon such scientific and practical problems as the definition of the concept of "use of force", as well as the development of basic components to ensure the proportionality of the use of force. The article "the use of force" was considered not only as the direct use of physical measures against persons or objects, but also the prevention or threat of their use in order to force people to a certain behavior or influence their behavior through physical or psychological influence, as well as with the aim of causing damage to property. The main components of ensuring the proportionality of the use of force were called professional and material training of law enforcement officers, preliminary planning of actions or the principle of prevention, as well as the existence of rules regulating in detail certain types of force.
Keywords: use of force; proportionality; law enforcement agencies; torture; human dignity; firearms; special equipment